2019
DOI: 10.1371/journal.pone.0222569
|View full text |Cite
|
Sign up to set email alerts
|

Validity of six consumer-level activity monitors for measuring steps in patients with chronic heart failure

Abstract: IntroductionAlthough numerous activity trackers have been validated in healthy populations, validation is lacking in chronic heart failure patients who normally walk at a slower pace, making it difficult for researchers and clinicians to implement activity monitors during physical activity interventions.MethodsSix consumer-level activity monitors were validated in a 3-day field study in patients with chronic heart failure and healthy individuals under free living conditions. Furthermore, the same devices were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
43
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 34 publications
(47 citation statements)
references
References 44 publications
3
43
0
1
Order By: Relevance
“…The two other studies assessed step accuracy of accelerometers by visual observation on the treadmill and during free walking at various speeds. They both found that at speeds slower than 3.0–3.6 km/h, the accuracy of the devices substantially deteriorates 29,58 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The two other studies assessed step accuracy of accelerometers by visual observation on the treadmill and during free walking at various speeds. They both found that at speeds slower than 3.0–3.6 km/h, the accuracy of the devices substantially deteriorates 29,58 …”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the step‐counting algorithms provided by various manufacturers are all proprietary and use different thresholds of acceleration to detect a step, which limits the comparability among studies using different devices 73 . Despite numerous validation studies showing that most commercially available accelerometers are more or less equal in general populations with normal gait, 74,75 other studies have reported that step‐counting accuracy deteriorates in patients with chronic conditions, particularly during slower gait speeds 58,76 . As such, steps can still remain a useful self‐monitoring metric for patients but should be avoided by researchers striving for high accuracy and reproducibility of their findings.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A strict comparison of our study findings with other research within this population was not possible due to the lack of such studies. On the other hand, studies have been conducted aiming to evaluate criterion validity in wrist-worn activity trackers among an elderly population [ 56 ] as well as among populations suffering from chronic cardiac conditions [ 57 , 58 ]. These reports also suggest an overestimation of energy expenditure.…”
Section: Discussionmentioning
confidence: 99%